Group A Streptococcal Endometritis: Report of an Outbreak and Review of the Literature - Ziad A Memish; Denise Gravel-Tropper; Catherine Oxley; Baldwin Toye; Gary E Garber (Canadian Journal of Infectious Diseases)
Two cases of group A streptococcus (gas) postpartum endometritis were diagnosed within 24 h following uncomplicated vaginal delivery. Investigation by the infection control service identified all 10 obstetric personnel who performed any invasive procedure on both cases. These personnel were questioned about a recent history of sore throat, skin lesions, vaginal or rectal symptoms. Throat and rectal cultures were obtained for gas from all 10 personnel. A carrier was identified among the personnel screened. This nurse was removed from direct patient care and treated with a two-week course of oral clindamycin and rifampin with documentation of carrier eradication of gas at the end of therapy, 30 days, 60 days and six months post-treatment. All three isolated strains were identical by restriction endonuclease analysis and by M and T typing. Rapid implementation of infection control measures were successful in arresting this outbreak, with no further cases of gas occurring in the subsequent year.